Prototype of electromagnetic actuator for continuously variable transmission for passenger car - Rahman, Mohammed Ataur; Sany, Ihsan; Rashid, Muhammad Mahbubur; Ismail, Ahmad Faris (2019)
Continuously variable transmission (CVT) system transmits the engine /battery power to the car driving wheel smoothly and efficiently. Car with current CVT produces some noise and slow acceleration to meet the car power demand. There are about jerky movement and non- uniform power transfers during initial acceleration and slope climbing or rattling noises during slow speeds. The problems of CVT incur due to the slow response of hydraulic pressure. A prototype electromagnetic actuator (EMA) has been designed and fabricated for the actuation of CVT system with the finance Ministry of Higher Education (MOHE) with Prototype Research Grants in 2016 (Project Reference:PRGS 2016-04-0035). The EMA has been fixed with the TOYOTA WISH CVT system and tested with the IIUM Test bed. The dynamic load of the vehicle, in accordance the road-load, has been applied on the EMA- CVT with an attachment. A load cell with a programable fuzy logic controller has been designed for making the EMA-CVT intellegent.Furthermore, Furthermore, the central manual switching system (CMSS) has ensured the EMA operation about 80% to actuate the CVT system in case of failure the intelligent system. The prototype has been found very silent in any vehicle dynamic operation and able to solve the problem of the conventional CVT that occurred during climing the slope and longer operational time. The CVT actuation time is recorded as 3 s and 3.5s for the gear ratio of 5 and 2.5 respectively. The supplied current to the EMA is recorded 12 A for the gear ratio 5 and 7A for 2.5. A lead acid battery pack of voltage 60V and capacity 67 Ah has been used to supply the current to the EMA through a fuze logic controller. The fast actuation time on gear changing indicates that the EMA-CVT has eliminated the power loss of the transmission about 80%. The efficiency of the EMA-CVT is considered as energy-efficient system for the vehicle (EEVS) which is in-line with the National Automotive Policy (NAP) 2014 and 2018. Based on the operation and integration of EMA and CVT, it is announced that EMA-CVT is new transmission system for the advanced automotive technology. This product has the potentiality to save dollars of the country from importing CVT. The price of EMA-CVT (RM5,000) over the price of Nissan- CVT (RM13,000), makes the EMA-CVT highly competitive.